Studying the Dynamics of Knowledge-Sharing Success Factors Based on Willing Criteria - Saeedeh Shokouhi; Soha Safaei; Zahra Shams Esfandabadi (مدیریت مهندسی و رایانش نرم)
One of the main bases of the knowledge management process is knowledge-sharing which means extended interpersonal interactions leading to distribution and absorption of knowledge and experience effectively and appropriately. In order to analyse the strengths and weaknesses of the knowledge-sharing process in an organization and designing policies to improve it, the factors affecting the success of this process should be determined. Considering the three sections "Will", "Can" and "May" in the Human Resources Productivity model and the dominance of the "Will" amongst them, in this research, effective factors on the knowledge-sharing process based on willing criteria is determined and analysed by studying the relevant literature. Then, dynamics and relationships among these factors are discussed and a conceptual model is provided. Important strategies are also suggested in this regard. As a case study, the proposed model is applied in an Iranian mother-specialized protein food company and its validity is confirmed by the experts.